2021
DOI: 10.3390/antibiotics10040446
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Daptomycin-Induced Eosinophilic Pneumonia in a Population with Osteoarticular Infection

Abstract: Background: Daptomycin-induced eosinophilic pneumonia (DEP) is a rare but severe adverse effect and the risk factors are unknown. The aim of this study was to determine risk factors for DEP. Methods: A retrospective cohort study was performed at the Bone and Joint Infection Unit of the Hospital Universitari Bellvitge (January 2014–December 2018). To identify risk factors for DEP, cases were divided into two groups: those who developed DEP and those without DEP. Results: Among the whole cohort (n = 229) we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…Among our cohort, only 1.7% of patients who received daptomycin for BJI developed a DIEP whereas they received a median daily dose of 8.2 mg/kg. This is lower than the 4.8% found in a recently published study by Soldevila-Boixader et al [ 25 ]. Unfortunately, in that study, dosages were only expressed in milligrams or total cumulative doses, and there is no information of dosages in milligrams per kilogram, which seems more relevant.…”
Section: Discussioncontrasting
confidence: 68%
“…Among our cohort, only 1.7% of patients who received daptomycin for BJI developed a DIEP whereas they received a median daily dose of 8.2 mg/kg. This is lower than the 4.8% found in a recently published study by Soldevila-Boixader et al [ 25 ]. Unfortunately, in that study, dosages were only expressed in milligrams or total cumulative doses, and there is no information of dosages in milligrams per kilogram, which seems more relevant.…”
Section: Discussioncontrasting
confidence: 68%
“…The rest of the cases were treated with less than 6 mg/kg/day of daptomycin for a median of 23 days [ 3 ]. Some of the risk factors identified by Soldevila et al for developing daptomycin-induced AEP include advanced age, high values of the Charlson comorbidity score, high total cumulative daptomycin dose, specifically more than 10 g, and prolonged therapy of more than two weeks [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five of the seven patients were also treated with systemic corticosteroids, and two patients reported EP recurrence after the re-administration of DAP. In another retrospective study [ 7 ], the risk factors for DAP-induced EP were age ≥ 70 years and duration of therapy > 14 days. In our study, the median age and the median number of days from DAP initiation to EP onset were identified as risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In an observational study including 102 patients with infectious endocarditis treated with a DAP dose of 8.2 mg/kg, three patients developed EP [ 14 ]. In a retrospective study [ 7 ], a total dose of DAP > 10 g was observed as a risk factor in an unadjusted analysis. Hayes et al hypothesized that DAP may cause EP by binding with the human pulmonary surfactant, resulting in its accumulation in the alveolar spaces at concentrations high enough to injure the epithelium and cause inflammation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation